2012
DOI: 10.1183/09031936.00097512
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography and pulmonary embolism severity index have independent prognostic roles in pulmonary embolism

Abstract: We analysed a cohort of patients with normotensive pulmonary embolism (PE) in order to assess whether combining echocardiography and biomarkers with the pulmonary embolism severity index (PESI) improves the risk stratification in comparison to the PESI alone.The PESI was calculated in normotensive patients with PE who also underwent echocardiography and assays of cardiac troponin I and brain natriuretic peptide. 30-day adverse outcome was defined as death, recurrent PE or shock. 529 patients were included, 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
1
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 16 publications
1
41
1
12
Order By: Relevance
“…In contrast to the majority of studies enrolling younger hemodynamically stable patients with PE [13,15,20,21,[24][25][26][27][28][29][30], we did not find a relationship between echocardiographic RV dysfunction and short-term clinical outcomes in our sample of elderly patients. In particular, the specific set of echocardiographic criteria recommended by the American Heart Association (presence of RV/LV end-diastolic diameter ratio >0.9 or RV hypokinesis) was not associated with adverse clinical events.…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast to the majority of studies enrolling younger hemodynamically stable patients with PE [13,15,20,21,[24][25][26][27][28][29][30], we did not find a relationship between echocardiographic RV dysfunction and short-term clinical outcomes in our sample of elderly patients. In particular, the specific set of echocardiographic criteria recommended by the American Heart Association (presence of RV/LV end-diastolic diameter ratio >0.9 or RV hypokinesis) was not associated with adverse clinical events.…”
Section: Discussioncontrasting
confidence: 54%
“…In our study, each of the 3 studied TTE findings was associated with 30‐day PE‐related mortality in unadjusted and adjusted models. A study of 529 patients with PE identified separate effects of PESI and TTE findings on 30‐day outcomes of patients with PE,3 while another recent study of 400 patients with PE by Hofmann et al did not find an independent association between TTE findings and outcomes 5. The association between RA enlargement and PE outcomes has been under recent investigation,13, 14 and may be potentially explained by right heart volume and pressure overload in the setting of acute PE.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that transthoracic echocardiography (TTE) could help in early risk stratification of patients with acute PE. Yet, the results have been inconsistent and the use of TTE in real life and its prognostic value have not been consistently studied 3, 4, 5, 6. We used the data from the RIETE (Registro Informatizado Enfermedad TromboEmbolica) registry to report the real‐world use and predictors of early TTE (within the first 72 hours from diagnosis) in patients with PE, and to explore the association between some of the main TTE findings and 30‐day PE‐related mortality in unadjusted and adjusted analyses.…”
Section: Introductionmentioning
confidence: 99%
“…16,24 A systemic review of the literature has shown that patients with RVD on echocardiography, increased levels of troponin or of B-type natriuretic peptide (BNP) and N-terminal pro-BNP (NT-proBNP), which could indicate numerous diseases such as heart failure or pulmonary hypertension, had an elevated short-term risk of adverse events compared with patients with normal levels of those parameters. [25][26][27][28] When used to identify low-risk patients, RVD on echocardiography had an NPV of 96% for a 30-day complicated outcome, 25 and the normal levels of BNP or NT-pro BNP were associated with an early mortality rate of 2.2% and 30-day mortality, survival was lower in the highrisk group compared with the low-risk group (log--rank test, P <0.0001; FIGURe 1A). Similarly, using the SI for predicting the overall 30-day mortality, survival was significantly lower in the high--risk group compared with the low-risk group (log-rank test, P <0.0001; FIGURe 1B).…”
mentioning
confidence: 99%
“…Previous studies reported a mortality rate of 0% to 2.8% in normotensive patients with PE, including a low-risk group classified using the sPESI. 24,25,29,30 In the studies of unstable patients with PE, the mortality rate was from 0% to 1.1%. 7,31 Both studies suggested that outpatient treatment was appropriate for low-risk patients.…”
mentioning
confidence: 99%